Rare Emphysematous Osteomyelitis of the Femoral Head: A Case Report and Literature Review - Xu Y; Wu G; Zhang G; Li D; Zhang L; Yang W (Infection and Drug Resistance)
Yuanyuan Xu,1 Guangrong Wu,1 Guomin Zhang,1 Dongxue Li,1 Lunyou Zhang,2 Wei Yang1 1Department of Radiology, The First People’s Hospital of Zunyi (The Third Affiliated Hospital of Zunyi Medical University), Zunyi, Guizhou, People’s Republic of China; 2Department of Pathology, The First People’s Hospital of Zunyi (The Third Affiliated Hospital of Zunyi Medical University), Zunyi, Guizhou, People’s Republic of ChinaCorrespondence: Wei Yang, Email coxsackie@163.comAbstract: Emphysematous osteomyelitis (EO) is a perilous infection of the femoral head. In this case, we present a 66-year-old male patient of Han ethnicity, who had lumbar disc herniation and type 2 diabetes mellitus. The patient reported severe pain in his lower back and right lower limb, which had worsened over the past 20 days. Despite undergoing invasive procedures such as regional anesthetic blocks and other traditional Chinese medical methods such as acupuncture and acupotomy, his condition deteriorated. Pain in the lumbar region was not relieved, and there was a new onset of pain in the right hip, groin, and thighs. Preliminary medical evaluation revealed normal body temperature but elevated levels of the inflammatory marker high-sensitivity C-reactive protein (hsCRP). In the imaging tests, computed tomography revealed air bubbles within the right femoral head, corresponding to the EO. Diabetes mellitus and malignant neoplasms have been well-established as predominant risk factors for EO, while iatrogenic interventions may serve as potential precipitating factors in disease pathogenesis. Our report underlines the critical role of radiologists in identifying EO through distinctive imaging features, such as the “pumice stone” sign. This highlights the need for further research to enhance our understanding, diagnosis, and management of EO.Keywords: emphysematous osteomyelitis, MRI, CT, acupotomy, diabetes